Observed Spatial and Temporal Behaviour of Seismic Rock Mass Response to Blasting - K. Woodward (The Southern African Institute of Mining and Metallurgy, 2015)
"SynopsisSeismically active mines generally experience an increase in seismic hazard due to rock mass instability following blasting. Re-entry protocols commonly include measures to limit the spatial and temporal exposure of personnel to increased seismic hazard induced by blasting. The management of periods of increased seismic hazard requires the development of re-entry protocols for a unique mining environment. Identifying mining conditions that may result in significant seismicity following blasting relies on retrospective analysis, which is often focused on seismicity occurring within a certain period after blasting and within a certain radius of the blast in the broader context of site-specific experience.The analysis of seismicity without considering blasting times and locations allows for the relationship between seismicity and blasting to be investigated without prior assumptions concerning dependency. To achieve independent analysis, seismicity that is clustered in space and time (referred to as a seismic sequence) must be identified by assessment utilizing only seismic parameters. An automated algorithm is implemented that assesses the timing, location, and quantity of seismicity to identify seismic sequences, represented by the time of the first event and mean location of all events in the sequence.The relationship between sequences and blasts is assessed by calculating the distance and time from each sequence to the closest blast in space and time. Establishing an independent classification between sequences and blasting provides insight into the unique cases where seismic sequences are remote and/or delayed with respect to blasts and identifies cases when sequences exhibit a weak relation to blasting. The nature of seismic responses to blasting has direct implications for the management of the increased seismic hazard associated with seismic sequences.The approach presented in this study contributes to the management of seismic hazard by providing empirical support for the relationship between seismic sequences and blasting. These relationships indicate the portions of sequences that can and cannot be practically managed using tactical approaches. Furthermore, the analysis of sequences reveals the nature and evolution of rock mass responses to blasting. These results have implications for the extent of spatial or temporal re-entry restrictions required for the optimal management of time-dependent rock mass response to mining."